Low Self-Control, Deviant Peer Associations, and Juvenile Cyberdeviance - Holt, Thomas J. (American journal of criminal justice, 2012)
Gottfredson and Hirschi’s ( 1990 ) general theory of crime and Akers’ ( 1998 ) social learning theory have received strong empirical support for explaining crime in both the physical and cyberworlds. Most of the studies examining cybercrime, however, have only used college samples. In addition, the evidence on the interaction between low self-control and deviant peer associations is mixed. Therefore, this study examined whether low self-control and deviant peer associations explained various forms of cyberdeviance in a youth sample. We also tested whether associating with deviant peers mediated the effect of low self-control on cyberdeviance as well as whether it conditioned the effect. Low self-control and deviant peer associations were found to be related to cyberdeviance in general, as well as piracy, harassment, online pornography, and hacking specifically. Deviant peer associations both mediated and exacerbated the effect of low self-control on general cyberdeviance, though these interactions were not found for the five cyberdeviant types examined.